Secular Volunteerism among Texan Emerging Adults: Exploring Pathways of Childhood and Adulthood Religiosity - DeAngelis, Reed T. (Religions, 2016)
Prior research suggests that religiosity, especially public religious participation, is related to greater volunteerism. However, less is known about religious transmission across the life course, in particular whether and how religiosity in childhood is linked to later life volunteerism. This study investigates a sample of emerging adults in South Texas (n = 701) with a high percent of Hispanic Americans (53 percent). Specifically, we examine pathways of childhood and emerging adulthood religiosity leading to secular volunteerism. Findings indicate that both childhood and emerging adulthood religiosity are associated with greater volunteerism, but the effects of childhood religiosity on emerging adulthood volunteerism are mediated through emerging adulthood religiosity. These findings provide further confirmation of the importance of childhood religiosity only insofar as religiousness persists into adulthood. In other words, we find that it is emerging adulthood religiosity that transmits childhood religiosity into greater secular volunteerism in later life. Furthermore, emerging adulthood public religiosity has the most robust direct effects on volunteerism.